Disaster Preparedness Amongst Emergency Pharmacists for the FIFA World Cup Qatar 2022™: A Cross-Sectional Survey - Isleem N; Naseralallah L; Koraysh S; Abu Ghalyoun A; Alnaimi S; Pallivalapila A; Al Hail M (Dove Medical Press, 2023)
Nour Isleem,1,* Lina Naseralallah,1,2,* Somaya Koraysh,1 Ahmad Abu Ghalyoun,1 Shaikha Alnaimi,1 Abdulrouf Pallivalapila,1 Moza Al Hail1 1Pharmacy Department, Hamad Medical Corporation, Doha, Qatar; 2School of Pharmacy, College of Medical and Dental Sciences, University of Birmingham, Birmingham, UK*These authors contributed equally to this workCorrespondence: Nour Isleem, Pharmacy Department, Hamad Medical Corporation, P.O.Box 42, Doha, Qatar, Tel +974 3100 3071, Email NIsleem@hamad.qaPurpose: The aim of this study is to assess the level of preparedness of pharmacists working in the emergency department at Hamad Medical Corporation (HMC) for any emergency disasters that may take place during the FIFA World Cup Qatar 2022™ by evaluating their awareness (A), attitude (A), and readiness (R).Methods: A cross-sectional quantitative observational study was conducted through a web-based survey. The survey was distributed among emergency pharmacists working in general hospitals under HMC. The questionnaire was composed of three major domains assessing awareness, attitude, readiness, as well as an additional domain to collect the participants' demographics. Student's t-test, analysis of variance, Pearson's correlation, and linear regression were used with an alpha level of 0.05.Results: Most pharmacists working in the emergency departments at HMC had high levels of awareness (76.9%), attitude (92%), and readiness (53.8%) for any emergency disasters that may occur during the FIFA World Cup 2022. Nonetheless, almost half of the respondents reported moderate level of readiness for emergency events. Pharmacists with > 10 years' practice experience had significantly higher AAR score compared to those with < 5 years' experience (P = 0.002). Significant direct positive correlations were found among the 3 AAR parameters (P < 0.05). Attitude was found to be a significant predictor of readiness (P < 0.05). A model composed of attitude and awareness could predict 12% of readiness score.Conclusion: Emergency pharmacists at HMC have high level of preparedness for any emergency disaster event during the World Cup. Future research should focus on the development of theory-based action framework for pharmacy departments during mass gathering events.Keywords: disaster preparedness, disaster management, emergency medicine, pharmacist, mass gathering, FIFA World Cup